Scrutinizing Emergency Curriculum in an Elementary School: A Case Study at SDN Wonotingal Semarang - Andika Wisnu (JENIUS (Journal of Education Policy and Elementary Education Issues), 2022)
The flexibility in implementing a curriculum adapting to the learning conditions and needs is one of the efforts undertaken by the Indonesian government to prevent the spread of Covid-19. This curriculum is referred to as the ‘Emergency Curriculum’, which is a simplification of the national curriculum. This current study delineates an overview of the preparation and the lessons taught during the implementation of the emergency curriculum due to the pandemic. This case study was carried out at SDN Wonotingal Semarang in the academic year 2020/2021. Data collection was carried out through observation, interviews, and documentation which validated data triangulation. This study indicates that the implementation of the emergency curriculum was a solution to the education unit's lack of preparedness to tackle the pandemic. The curriculum structure is created by taking into account a range of factors as guidelines in schools. Flexible learning is the answer to the challenges that may arise during an emergency. Life skills education becomes an alternate achievement that students must acquire in the new normal. To sum up, this study offers an alternate perspective on curriculum development and learning during the pandemic, particularly in elementary schools.